Labour as Entrepreneurs: The Ambivalent Role of Labour in Restructuring in the Polish Steel Industry - Trappman, Vera (Warsaw Forum of Economic Sociology, 2011)
The paper analyses steel restructuring at one of the major steel companies in Poland. It traces the restructuring history from the 1990s up to recent times, arguing that restructuring was heavily influenced by EU-accession conditionality and by the sector-oriented policy of Polish trade unions. While steel restructuring is often considered a major success story in Poland, this article, basing its argument on the life trajectories of the redundant workers, highlights the downside of a sectoral approach which operates at the expense of regional restructuring.